MathRevolution wrote:
\(xy=?\)
1) \(y=x-1\)
2) \(y^2=-|x-1|\)
We need to find product of x and y
1)
y = x - 1
we do not know the value of either of x or y
Hence Insufficient
2)
y^2 = - | x-1 |
Case 1 : when | x - 1 | is negative
y^2 = -[-(x - 1)]
y^2 = x - 1 ....................equation 1
Case 2 : when | x - 1 | is positive
y^2 = -[(x - 1)]
y^2 = -x + 1 ....................equation 2
equation 1 = equation 2 (as both are equal to y^2 )
x-1 = -x + 1
x = 1
Now keeping value of x in any of the 2 equations
y^2 = -x + 1 (Now x = 1)
y^2 = -1 + 1
y^2 = 0 so y is also 0
It means x * y = 0
Hence B
Thanks